TELE-FISIOTERAPI SEBAGAI PENDEKATAN INOVATIF DAN ADAPTIF TERHADAP KUALITAS HIDUP PASIEN STROKE SELAMA PANDEMI COVID-19 (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2021)
COVID-19 pandemic is the biggest challenge for physiotherapists in providing health services to stroke patients, that physiotherapists must take innovative and adaptive approaches to monitor patient progress. Currently, tele-physiotherapy is a global trend that can be applied by physiotherapists during the COVID-19 pandemic to improve secondary health-care for stroke patients. This study aims to determine the effect of tele-physiotherapy on the quality of life of stroke patients during the COVID-19 pandemic. The design of this study was a systematic literature review, the independent variable is tele-physiotherapy and the dependent variable is quality of life with stroke patients as the study subjects. Literature search was conducted on four search engines, namely PMC, ProQuest, Google Scholar, and Europe PMC. There are 8 eligible literature obtained by the PICOS method. The types of tele-physiotherapy provided are the MERLIN system, GR Mirror Therapy, Home-based individual's exercise, Fitness and Mobility Exercise program, GCS, Home-Based Rehabilitation, Home Exercise Program (tele-rehabilitation), and Supervised Home-based Self-rehabilitation program. There is an effect of tele-physiotherapy on the quality of life of stroke patients during the COVID-19 pandemic.